Translational models for vascular cognitive impairment: a review including larger species. Issue 1 (December 2017) - Hainsworth, Atticus; Allan, Stuart; Boltze, Johannes; Cunningham, Catriona; Farris, Chad; Head, Elizabeth; Ihara, Masafumi; Isaacs, Jeremy; Kalaria, Raj; Lesnik Oberstein, Saskia; Moss, Mark; Nitzsche, Björn; et al.
Abstract Background Disease models are useful for prospective studies of pathology, identification of molecular and cellular mechanisms, pre-clinical testing of interventions, and validation of clinical biomarkers. Here, we review animal models relevant to vascular cognitive impairment (VCI). A synopsis of each model was initially presented by expert practitioners. Synopses were refined by the authors, and subsequently by the scientific committee of a recent conference (International Conference on Vascular Dementia 2015). Only peer-reviewed sources were cited. Methods We included models that mimic VCI-related brain lesions (white matter hypoperfusion injury, focal ischaemia, cerebral amyloid angiopathy) or reproduce VCI risk factors (old age, hypertension, hyperhomocysteinemia, high-salt/high-fat diet) or reproduce genetic causes of VCI (CADASIL-causing Notch3 mutations). Conclusions We concluded that (1) translational models may reflect a VCI-relevant pathological process, while not fully replicating a human disease spectrum; (2) rodent models of VCI are limited by paucity of white matter; and (3) further translational models, and improved cognitive testing instruments, are required.